Structural, Nursing, and Physician Characteristics and 30-Day Mortality for Patients Undergoing Cardiac Surgery in Pennsylvania*. Issue 9 (September 2017) - Lane-Fall, Meghan B.; Ramaswamy, Tara S.; Brown, Sydney E. S.; He, Xu; Gutsche, Jacob T.; Fleisher, Lee A.; Neuman, Mark D.
Abstract : Objective: Cardiac surgery ICU characteristics and clinician staffing patterns have not been well characterized. We sought to describe Pennsylvania cardiac ICUs and to determine whether ICU characteristics are associated with mortality in the 30 days after cardiac surgery. Design: From 2012 to 2013, we conducted a survey of cardiac surgery ICUs in Pennsylvania to assess ICU structure, care practices, and clinician staffing patterns. ICU data were linked to an administrative database of cardiac surgery patient discharges. We used logistic regression to measure the association between ICU variables and death in 30 days. Setting: Cardiac surgery ICUs in Pennsylvania. Patients: Patients having coronary artery bypass grafting and/or cardiac valve repair or replacement from 2009 to 2011. Interventions: None. Measurements and Main Results: Of the 57 cardiac surgical ICUs in Pennsylvania, 43 (75.4%) responded to the facility survey. Rounds included respiratory therapists in 26 of 43 (60.5%) and pharmacists in 23 of 43 (53.5%). Eleven of 41 (26.8%) reported that at least 2/3 of their nurses had a bachelor's degree in nursing. Advanced practice providers were present in most of the ICUs (37/43; 86.0%) but residents (8/42; 18.6%) and fellows (7/43; 16.3%) were not. Daytime intensivists were present in 21 of 43 (48.8%) responding ICUs; eight of 43 (18.6%) had nighttime intensivists. Among 29, 449 patients, there was no relationship between mortality and nurse ICU experience, presence of any intensivist, or absence of residents after risk adjustment. To exclude patients who may have undergone transcatheter aortic valve replacement, we conducted a subgroup analysis of patients undergoing only coronary artery bypass grafting, and results were similar. Conclusions: Pennsylvania cardiac surgery ICUs have variable structures, care practices, and clinician staffing, although none of these are statistically significantly associated with mortality in the 30 days following surgery after adjustment. Abstract : Supplemental Digital Content is available in the text.